2002
DOI: 10.1007/s00114-002-0322-2
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond time-resolved spectroscopy of elementary molecular dynamics

Abstract: Femtosecond time-resolved coherent anti-Stokes Raman spectroscopy (CARS) is applied in order to prepare and monitor laser-induced vibrational coherences (wave packets) of different samples mainly in its electronic ground state but also in excited states. The time evolution of these wave packets gives information on the dynamics of molecular vibrations. In a first example the femtosecond (fs) CARS transients of iodine are investigated. By changing the relative delay between the applied laser pulses of this non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 55 publications
(44 reference statements)
0
18
0
Order By: Relevance
“…Closed-loop learning algorithms are exploited in CC to generate complex optical phases in order to optimize specific reaction pathways. CC has been used as a tool in the control of dynamic processes [17][18][19][20][21], and it explains how a specific state can be selectively populated, for example, to attain 100% population transfer [22][23][24][25], and recent studies have shown the possibility of having enhancements even higher than 100% [26][27][28][29][30][31][32][33][34][35]. QCS also exploits tailored excitation but differs from CC in its applications [30,36].…”
Section: Introductionmentioning
confidence: 99%
“…Closed-loop learning algorithms are exploited in CC to generate complex optical phases in order to optimize specific reaction pathways. CC has been used as a tool in the control of dynamic processes [17][18][19][20][21], and it explains how a specific state can be selectively populated, for example, to attain 100% population transfer [22][23][24][25], and recent studies have shown the possibility of having enhancements even higher than 100% [26][27][28][29][30][31][32][33][34][35]. QCS also exploits tailored excitation but differs from CC in its applications [30,36].…”
Section: Introductionmentioning
confidence: 99%
“…With the improvement of temporalspectral distribution of the SC, the simultaneously detectable spectral range of system can be further extended, which is called the ultra-broadband T-CARS and will be discussed in detail in the next section. [84,96] With a broadband T-CARS spectroscopy, we can obtain more specificities of the sample, not only the vibrational spectra reflecting the molecular structure and compositions, but also the dephasing time of various molecular vibrational modes reflecting the molecular responses to the external micro-environment, which are especially favorable for the study of the complicated interaction processes between molecules and their micro-environment such as solute-solvent interactions [108,109] , molecular dynamics [110][111][112][113][114] , supramolecular structures [115] and excess energy dissipations in the fields of biology, chemistry and material science [64,[116][117][118] .…”
Section: Suppression Of Nrb Noise In Broadband Cars With Scmentioning
confidence: 99%
“…Ro-vibrational Raman spectroscopy enables researchers to directly prepare and monitor the molecular vibrational and rotational behaviors in the molecular ground and excited states. 1,2 In this communication, we demonstrate that the transient stimulated Raman scattering (SRS) induced by intense laser pulse enables the tracking of the molecular structural deformation and relaxation. Under the intense offresonance pump pulse excitation (10 11 -10 12 W/cm 2 ), molecules can experience large torques to drive molecular alignment and deformation within a time scale of ∼100 fs.…”
mentioning
confidence: 97%